A new rapid and sensitive assay for detecting the T315I BCR-ABL kinase domain mutation in chronic myeloid leukaemia. Issue 7 (27th June 2008) - Khorashad, J S; Thelwell, N; Milojkovic, D; Marin, D; Watson, J A; Goldman, J M; Apperley, J F; Foroni, L; Reid, A G
Abstract : A significant minority of chronic myeloid leukaemia patients eventually develop resistance to imatinib, often as a result of point mutations within the BCR-ABL kinase domain. Second-line tyrosine kinase inhibitors (TKIs) are effective against mutations that confer imatinib resistance; however, the T315I BCR-ABL mutant has proved resistant to all available TKIs. An assay facilitating early identification of BCR-ABL T315I would therefore aid in identifying high-risk patients who may benefit from alternative therapy. This report describes the development of a sensitive T315I mutation detection methodology based on real-time PCR with self-probing fluorescent primers. The technique demonstrated complete concordance with direct sequencing, correctly identifying 34 T315I-positive samples from a total of 61 samples screened. In a limiting dilution assay, the mutated clone was detectable to a level of 1% of total cells. The data show that Scorpions PCR enables rapid screening for BCR-ABL T315I in chronic myeloid leukaemia patients and is appropriate for use in a clinical setting.